Features of the postoperative period in patients with uncomplicated forms of ureterolithiasis - O. Nikitin; I. Komisarenko (Kazimierz Wielki University, 2023)
In order to study the possibilities of non-drainage management of the postoperative period in patients with uncomplicated ureteral stones, we analyzed the results of treatment of 198 patients with uncomplicated ureterolithiasis, in whom it was decided to refuse stenting of the upper urinary tract. In the uncomplicated course of ureterolithiasis, in most cases (68.2% of patients) in the postoperative period, there is no need for drainage of the upper urinary tract with stent. At the same time, in 31.8% of patients when a stent was not installed in the postoperative period, complications occurred that significantly affected the duration and cost of treatment. In the future a more rigorous consideration of risk criteria is needed to make a decision on non-drainage management of the postoperative period in patients with uncomplicated ureteral stones.